Pengaruh Sosial Media Marketing Terhadap Penjualan Produk Iphone di Negri Ponsel Teluk Kuantan - Mai Yora Debby Silvia; Eka Komalasari (SYNERGY: Jurnal Bisnis dan Manajemen, 2024)
This study aims to determine the influence of social media marketing on the sale of Iphone products at the Teluk Kuantan Mobile State Store. The type in this study uses a quantitative approach. The population in this study is the people of Teluk Kuantan City and its surroundings who have bought Iphone products at the Negri Mobile Store. The sample in this study amounted to 100 respondents using sampling techniques. Data collection is carried out by the distribution of questionnaires. Data analysis techniques use validity tests, reliability tests, normality tests, linearity tests, heterokedacity tests, simple regression analysis, determination coefficient tests and t tests. The results of the analysis show that social media marketing has a positive and significant effect on iPhone product sales. The result of the coefficient of determination shows that the value of the coefficient (R Square) is 0.254, which means that sales of iPhone products are influenced by social media marketing before 25.4% with weak criteria, while the remaining 100% - 25.4% = 74.6% is influenced by other factors, one of which is a high lifestyle, product quality, and brand image